Analisis Pengelolaan Uang Bulanan Mahasiswa Prodi Pendidikan Ekonomi FKIP Unpatti: Strategi, Gaya Hidup, dan Tantangan Finansial - Nagwaem, Dorima Simson; Louhenapessy, William George Mozes; Sinay, Francisca Riconita (Universitas Pattimura, 2022)
This study aims to analyze the management of monthly finances by students of the Economic Education Study Program at FKIP Unpatti, as well as the influencing factors. The research is grounded in the importance of financial management skills for students who are beginning to live independently. A qualitative approach with a case study design was employed to explore in depth the behaviors and strategies students use to manage their finances. Data were collected through in-depth interviews with eight purposively selected students. Thematic analysis was used to identify patterns in financial management, saving habits, lifestyle influences, and the challenges they face. The findings reveal that most students do not yet have structured financial habits. The main obstacles are a consumerist lifestyle, lack of discipline, and limited practical financial literacy. Students with better self-control and planning skills tend to maintain more stable financial conditions. This study suggests the need for applied and behavior-based financial education to enhance students’ capacity to manage their money effectively.